Prosodi Semantik Nomina Qalb dalam Al-Qur'an: Kajian Linguistik Korpus - Maula, Ismatul; Rizalman, Mhd. (Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study investigates the semantic prosody of the noun qalb in the Qur'an using a corpus-based linguistic approach. The research aims to identify its collocational patterns, evaluate its positive, negative, and neutral prosodic tendencies, and analyze how contextual features influence its semantic nuances. Using data extracted from the Quranic Arabic Corpus, all 132 occurrences of qalb in their various morphological forms were examined. The analysis applies Partington's attitudinal-functional model and Hunston's context-based interpretation to classify collocates and determine evaluative meanings. The findings reveal that qalb is most frequently associated with negative prosody, such as hardness, deviation, disease, and heedlessness, while positive prosody appears in contexts of faith, tranquility, and purity, with a small portion showing neutral usage. Overall, the study concludes that the meaning of qalb in the Qur'an is dynamic and shaped by its collocations and contextual distribution.